PENINGKATAN LITERASI KEUANGAN DOSEN MELALUI PELATIHAN ANALISIS FUNDAMENTAL SAHAM - Eureka Try Zarazwanty R Laega; Leonardo Davidsi Sipayung; Muhammad Novrizal Ramadhan; Andhi Febisatria (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service program aimed to improve lecturers’ financial literacy through fundamental stock analysis training at Universitas Negeri Makassar. The program was conducted in response to the gap between increasing financial inclusion and adequate levels of financial literacy, including among higher education lecturers. The training applied a participatory approach using a learning by doing method and utilized audited financial statements of publicly listed companies as practical learning materials. Program evaluation was carried out descriptively by comparing pre-test and post-test results and administering a participant satisfaction questionnaire. The results show an increase in the average financial literacy score from 45 in the pre-test to 85 in the post-test, representing a 40-point improvement. In addition, lecturers’ interest in stock market investment reached 68 percent, with an average satisfaction score of 4.7 on a five-point Likert scale. These findings indicate that practice-based training is effective in enhancing lecturers’ financial literacy.